The System of Energy Security in the Russian Northern Regions - ELYAKOVA, Izabella Damdinovna; PAKHOMOV, Alexander Alekseevich; DARBASOV, Vasiliy Romanovich; BARAKHOVA, Vera Vasilievna; ELYAKOV, Aleksandr Lvovich; MOSKVITINA, Ekaterina Nikolaevna (Journal of Advanced Research in Law and Economics, 2019)
The objectives of article are to study the foundations and conceptual approaches to ensuring energy security, to disclose the essence, principles of energy policy in the field of ensuring energy security as an integral part of the economic security of the state (region), to analyze the existing methods for evaluating energy security, and to offer a conceptual approach to the formation of a system for ensuring the region’s energy security with regard to the specificity of energy functioning in the Far North of Russia. Based on the study of theoretical foundations and methodological approaches to ensuring regional energy security are proposed: the development and adoption of a concept for ensuring energy security in the Republic of Sakha (Yakutia); the author's definition of the concept of the ‘region’s energy security’; an improved conceptual approach to the development of a system for ensuring the region’s energy security; a structural scheme for the organization and effective management of the energy security system in the Republic of Sakha (Yakutia).